ANALISIS PENYEBAB HUMAN ERROR TERHADAP KEJADIAN KECELAKAAN PADA TEKNISI DI PERUSAHAAN OTOMOTIF X, SEMARANG - Majida Wikaning Gati; Ida Wahyuni; Ekawati Ekawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2020)
Abstract: Two of thirds of accident cases are caused by Human Error. Human Error is very closely related to the actions taken by humans. Humans have limitations on their capacities such as seeing, paying attention, remembering, processing, and acting in a relevant manner that influences the decision making process of each individual and contributes to accidents with varying degrees of severity. One of them is in the automotive industry that requires high accuracy and accuracy in work and has the potential for danger both from environmental factors, tools, and management guidelines in pursuing production targets. The purpose of this research is to analyze the relationship between the factors that cause human error in the event of an accident to a technician at automotive company X, Semarang. This research is a quantitative study using an analytic observational study design and cross sectional approach. The population in this study were 44 technicians. The sampling technique used is total sampling technique in which the number of samples studied is equal to the existing population. Based on the Chi-Square statistical test results obtained that there is no relationship between threats (0.667> ρ value), situation awareness (0.088> ρ value), and action error (0.284> ρ value) with accident events. The biggest contribution to the main causes of accidents is teamwork, misunderstanding, and misinformation done by technicians.